2022
DOI: 10.3390/ani12162129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Immunomodulatory Feed Additive in Mitigating the Stress Responses in Lactating Dairy Cows to a High Concentrate Diet Challenge

Abstract: Dairy cows are often exposed to multiple stressors in a lactation-cycle, with sub-acute ruminal acidosis (SARA) a frequent example of nutritional stress. SARA affects ruminal and intestinal equilibrium resulting in dysbiosis with localized and systemic inflammation impacting animal health and productivity. OmniGen-AF (OMN, Phibro Animal Health Corporation, Teaneck, NJ, USA) is a feed product recognized for modulating innate immune function, especially during periods of stress. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…The TMR fed was adequate in terms of nutrient composition ( 36 ), and particle size (peNDF = 19.52 ± 2.18% of DM) was in line with previous studies based on similar rations ( 37 40 ). Fecal composition was normal for a cow in this lactation phase and the apparent total tract digestibility of the different nutrients indicates a good level of digestion ( Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…The TMR fed was adequate in terms of nutrient composition ( 36 ), and particle size (peNDF = 19.52 ± 2.18% of DM) was in line with previous studies based on similar rations ( 37 40 ). Fecal composition was normal for a cow in this lactation phase and the apparent total tract digestibility of the different nutrients indicates a good level of digestion ( Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…Straczek et al ( 58 ) reported that Simmental cows have a greater capacity to adjust the NEB state compared to Holsteins, restoring earlier the BCS loss after the lactation peak. Consequently, cows with good conditions at the onset of second lactation are more prone to perform better along the lactation and to be more resilient to the different metabolic disorders and reduced fertility ( 65 ). It is worth considering that farmers rearing Simmentals may decide to cull cows with higher muscularity at a certain point for beef purposes in order to increase the herd profit.…”
Section: Resultsmentioning
confidence: 99%
“…Variables that did not comply with the above assumptions were normalized using the BoxCox transformation. 23 When significance was detected (P < .05), the results were separated using Tukey's multiple comparison test.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the residuals were checked for an approximately normal distribution. Variables that did not comply with the above assumptions were normalized using the BoxCox transformation 23 …”
Section: Methodsmentioning
confidence: 99%